2007
DOI: 10.1021/ma070297m
|View full text |Cite
|
Sign up to set email alerts
|

Control of Nanostructure in Mixtures of Block Copolymers:  Curvature Control via Cosurfactant Effects

Abstract: We aim to elucidate the cosurfactant effects, which are expected when junctions of two block copolymers share a common microdomain interface, on morphology and phase behavior of mixtures. Especially this paper addresses the effects involved for binary mixtures composed of polystyrene-block-polyisoprene having about equal molecular weights but complementary compositions, one forming polystyrene (PS) cylinders in polyisoprene (PI) matrix and the other forming PI cylinders in PS matrix. Transmission electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 38 publications
1
60
0
Order By: Relevance
“…The hPS homopolymers also have low dispersity indices (smaller than 1.10). It has been reported and theoretically verified that the introduction of block length dispersity enhances the stability of discrete domains to higher volume fractions . The SCFT model applied here assumed perfectly monodisperse blocks.…”
Section: Resultsmentioning
confidence: 80%
“…The hPS homopolymers also have low dispersity indices (smaller than 1.10). It has been reported and theoretically verified that the introduction of block length dispersity enhances the stability of discrete domains to higher volume fractions . The SCFT model applied here assumed perfectly monodisperse blocks.…”
Section: Resultsmentioning
confidence: 80%
“…10,11 Experiments have shown that it is possible to obtain bicontinuous and cocontinuous phases by blending suitable DBCs-typically an asymmetric copolymer and a symmetric copolymer. [12][13][14] It was also shown that blending two symmetric DBCs does not always lead to a lamellar phase, but also to a spongy phase. Hashimoto and co-workers 13, 14 studied a binary blend of asymmetric and symmetric DBCs in detail, and found an unidentified bicontinuous phase in between cylinder and lamellae.…”
Section: Introductionmentioning
confidence: 99%
“…2 In that article, they conclude that in these inherently polydisperse blends ''the quality of the organization and the sharpness of the interfaces are not affected by the mixing.'' Since then, there has been much work, both experimental 3 and theoretical, 4 on the phase behavior of binary blends of block copolymers. The upshot of these efforts has been that the binary blends can be treated using ''a one-component approximation'' 4 provided the components in the blend do not differ too much in molecular weight or composition.…”
mentioning
confidence: 99%